Stock Market Prices and Volumes of Sales - Ying, Charles C. (Econometrica, 1966)
or vice versa will inevitably yield incomplete if not erroneous results. SUMMARY THE PRESENT investigation is a part of a study of the stock market which is motivated by three basic considerations: (1) Existing demand theory is inadequate for analyzing the problem of speculative prices and thus incapable of providing a valid prediction theory for this type of price mechanism. (2) The volume of sales in a commodity market has an economic significance in its own right and thus deserves much more attention by economists than it has received so far. (3) Prices and volumes of sales in the stock market arejoint products of a single market mechanism, and any model that attempts to isolate prices from volumes or vice versa will inevitably yield incomplete if not erroneous results. While the theoretical model and its implications will be presented elsewhere, the empirical results reported here serve as a basis for the proposed theory. Among the significant results so far found are: (1) A small volume is usually accompanied by a fall in price. (2) A large volume is usually accompanied by a rise in price. (3) A large increase in volume is usually accompanied by either a large rise in price or a large fall in price. (4) A large volume is usually followed by a rise in price. (5) If the volume has been decreasing consecutively for a period of five trading days, then there will be a tendency for the price to fall over the next four trading days.